Development of digital competencies towards improving performance of ministry of agrarian and spatial planning: insight from Indonesia - Heri Mulianto; Mohammad Syamsul Maarif; Nimmi Zulbainarni; Nur Hasanah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Digital competency is considered a new organizational priority in managing people in public institution. The purpose of this research was to examine the role of digital competence with support of digital leadership, transformation and digital culture can contribute for increasing ministry of agrarian and spatial performance. This research applied a quantitative approach by collecting data from 317 lecturers who worked at ministry of agrarian and spatial in Jakarta area. Purposive sampling was employed to gather data using online questionnaires. Next, partial least square structural equation modeling (PLS-SEM) was used to examine this data. The results showed that systematically developing each employee's digital competency creates a new organizational culture known as "digital culture," which in turn leads to the organization's digital transformation. To emphasize the significance of digital competence, digital culture, digital transformation, and digital culture in changing the nature and caliber of Indonesia's Ministry of Agriculture and Spatial Planning.